VALUE OF A PROFAYLING IN THE MODERN WORLD. TECHNOLOGY OF INCONGRUENCE DETECTION - I. N. Merzlikin (Научный вестник МГТУ ГА)
In the article the analysis of contact problems is carried out, the general recommendations and special psychological technicians acquaintance with which can be used by a wide range of persons and experts in the field of complex safety are called, and conclusions are also drawn on the need of acquiring the skills of a profiling by the persons dealing with problems of safety as it allows to reduce the quantity of potential problems and negative successions of events in the sphere of aviation safely.